Marco textual y desarrollo de la comprensión de textos académicos en inglés - Rosas, Minerva Concepción; Jiménez, Pablo Patricio; Sáez, Carmen Gloria (Colombian Applied Linguistics Journal, 2017)
This quasi-experimental study used samples naturally formed by three first year regular courses of a Chilean university. The experimental group included Aquaculture Engineer students and the control groups included Marine Biology and Environmental Engineer students. Our aims were to describe the elements that have an impact in the complexity of academic English texts in the Aquaculture area; to determine the effectiveness of a teaching learning model using cognitive activities (strategies) based on the analysis of scientific articles in this discipline; and finally to compare and analyse the reading comprehension strategies of academic texts written in English developed by the experimental and control groups following the intervention period. With this aim in mind we elaborated the text framework concept. We used quantitative and qualitative methodology to gather data. The quantitative instrument–a pre/post test–measured the improvement achieved by the experimental group in a 36-hour intervention period. The qualitative instruments included a questionnaire and a focus group to find out about the students’ beliefs about written text comprehension strategies in L1 and L2. As a result, we identified the factors that determine the complexity of Aquaculture academic texts, we detected the students’ difficulties when reading academic English texts and confirmed that the experimental group achieved a better development of reading comprehension strategies than the control groups when comparing both tests.